2021
DOI: 10.5194/acp-21-13011-2021
|View full text |Cite
|
Sign up to set email alerts
|

Opinion: The germicidal effect of ambient air (open-air factor) revisited

Abstract: Abstract. The term open-air factor (OAF) was coined following microbiological research in the 1960s and 1970s which established that rural air had powerful germicidal properties and attributed this to Criegee intermediates formed in the reaction of ozone with alkenes. We have re-evaluated those early experiments applying the current state of knowledge of ozone–alkene reactions. Contrary to previous speculation, neither Criegee intermediates nor the HO radicals formed in their decomposition are directly respons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Rather, they believed it to be due to a mixture of unidentified reactive chemicals. A recent review of the evidence reached the same conclusion [17]. While the causative agents have yet to be appropriately identified, the most likely candidates that contribute to the OAF may be a range of distinct germicides which are formed when alkenes in the air react with ozone.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Rather, they believed it to be due to a mixture of unidentified reactive chemicals. A recent review of the evidence reached the same conclusion [17]. While the causative agents have yet to be appropriately identified, the most likely candidates that contribute to the OAF may be a range of distinct germicides which are formed when alkenes in the air react with ozone.…”
Section: Discussionmentioning
confidence: 84%
“…By the 1970s, scientists had concluded that the OAF was not a single molecule [15] but a mixture of highly reactive chemical species which varied in composition [16]. The authors of a 2021 review paper on the subject supported this position, arguing that no single molecule or class of molecules can achieve the level of bactericidal activity reported in the Porton Down experiments [17]. One potential component of the OAF, the hydroxyl radical (HO), has been generated artificially and used to kill airborne pathogens [18][19][20][21].…”
Section: The Open-air Factormentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that both ozonolysis ,, and autoxidation reactions of lipid aerosol impact air quality and climate. , In particular, organic peroxide formation in aerosol has drawn substantial research attention recently. Not only may it affect the oxidizing ability of the atmosphere through decomposition, but also ROS exposure through inhalation of particulate matter is often linked to aerosol toxicity. As well, the presence of lipid-base peroxides in the ambient air could also contribute to the germicidal power of the atmosphere …”
Section: Results and Discussionmentioning
confidence: 99%
“…Lastly, the pandemic prompted a re-examination of an overlooked aspect of our atmosphere that it has an as-yetunidentified germicidal component referred to as the Open Air Factor (Cox et al, 2021). In particular, it was shown many decades ago that fresh air led to better outcomes for tuberculosis patients and injured World War I soldiers than indoor air.…”
Section: Multiphase Chemistry and Human Healthmentioning
confidence: 99%